Effectiveness of removing heavy metals by bacteria from water solutions - Loc, Nguyen Thi Bich (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The research on the effectiveness of removing heavy metals from water solutions by bacteria was carried out at the laboratory of the Institute of Environmental Engineering of the University of Zielona Góra in 2007-2008. The research covered bacterial strains isolated from sludge, soil and water. The tests concerned the effect of 3 heavy metals: Pb (0,1%), Cu (0,1%) and Zn (0,1%).
Keywords: bakterie; metale ciężkie; usuwanie metali ciężkich; bacteria; heavy metals; removing heavy metals